Population and Development Report - United Nations (United Nations, 2010)
This publication is one of a series of analytical Reports issued by the Population and Social Development Section of the Social Development Division at the Economic and Social Commission for Western Asia (ESCWA). It aims to deepen knowledge of the interrelation between population and development issues. The fourth edition of this Report is issued as one of the work programme activities of the Population and Social Development Section. These activities stress the importance to treat youth as a distinct sociodemographic group that needs to be targeted by specific national policies.